Effect of testosterone therapy on the female voice. (3rd March 2016) - Glaser, R.; York, A.; Dimitrakakis, C.
Abstract: Objectives This prospective study was designed to investigate the effect of testosterone, delivered by subcutaneous implants, on the female voice. Methods Ten women who had opted for testosterone therapy were recruited for voice analysis. Voices were recorded prior to treatment and at 3 months, 6 months, and 12 months while on testosterone therapy. Acoustic samples were collected with subjects reading a sentence, reading a paragraph, and participating in a conversation. Significant changes in the voice over time were investigated using a repeated-measures analysis of variance with the fundamental frequency ( F 0 ) as a response variable. Demographic variables associated with characteristics of the voice were assessed. Results There were no significant differences in average F 0 related to smoking history, menopausal status, weight, or body mass index. There was no difference in average fundamental speaking frequency (sentence, paragraph, conversation) between the pre-treatment group and any post-treatment group at 3 and 12 months. There was an increase in sentence speech F 0 at 6 months. Two of three patients with lower than expected F 0 at baseline improved on testosterone therapy. Conclusion Therapeutic levels of testosterone, delivered by subcutaneous implant, had no adverse affect on the female voice including lowering or deepening of the voice.